THE ROLE OF TERRITORIAL COHESION AS THE BASIS OF EUROPEAN SPATIAL PLANNING - Berezi Elorrieta (European Regional Science Association (ERSA), 2011)
The European Union regional policy has undoubtedly been a key to the European integration process. Its main purpose, originally, was to correct territorial imbalances between different EU states and regions. However, cohesion policy is today one of the most important tools to develop the Lisbon Strategy objectives (closely related to economic competitiveness), in a process called by some authors the 'Lisbonisation' of EU policies. The importance recently gained as a tool to promote competitiveness has allowed 'to save' the cohesion policy from the budget cuts supported by some net contributor countries. Moreover, since the entry into force of the Treaty of Lisbon, the cohesion policy is a shared competence between the EU and Member States, which gives the Commission a right of initiative to address cohesion policy recommendations. For a better implementation of the Lisbon Strategy, a greater territorialization of the actions as well as a better territorial governance between different institutional levels are needed, since the economic competitiveness is based on optimizing the regional territorial capital and on the capacity for resource mobilization. Thus, while cohesion policy originally lacked of a territorial approach, currently it is one of the policies with higher territorial impact. Consequently, from the French approach of aménagement du territoire, it means a real operational capability on spatial planning by the EU. Through this, the Union could overcome the need of financing and the lack of competence on territorial matters. In fact, although the term 'spatial planning' is almost banned in the EU language, the influence of European level on countries and regions spatial planning is increasing. Therefore, territorial cohesion, as a more neutral and vague concept, could turn into the 'Trojan Horse' by which the EU would exercise a real European spatial planning. This paper is aimed to analyze the development of EU cohesion policy, focusing in the role that it plays nowadays in territorial matters. Indeed, the new economic and institutional context could have a great influence on its function in a near future, acting as a framework for a real European spatial planning.
Keywords: 330